DIMENSI TANDA DALAM PERSPEKTIF ANALITIKA BAHASA LUDWIG WITTGENSTEIN DAN PENGARUHNYA DALAM TANDA KONTEMPORER - Mustansyir, Rizal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2012)
This article focused on Wittgenstein’s thought about sign. The thinking of sign is developed in semiotics tradition. Semiotics and philosophy of language are different tradition, but they have similarity, namely concern with problem of meaning. Wittgenstein’s thought in his two periods understood about sign in different way.Wittgenstein I said that sign of complexity is not arbitrarily resolved in the analysis, in such a way that its resolution would be different in every propositional structure. According to Wittgenstein II, not all signs have impressed themselves on subject so strongly. A sign in the algebra of logic form instance can be replaced by any other one without exciting a strong reaction in subject. Nowadays, signs in contemporary culture are developing into confusing signs, pseudo-signs, eloquent-signs, and codeswitching.